PRESSURE ANOMALIES AROUND CYLINDRICAL OBJECTS IN SIMPLE SHEAR - Tenczer V.; Stuwe K.; Barr T.D. (My University, 2001)
We model the pressure distribution around cylindrical objects in simple shear deformation using the finite element method in two dimensions and present an analytical solution for a special case. Parameter space is explored numerically for viscosity contrast between object and matrix, η, and for the non-linearity of flow, as expressed by n. We show that the geometry and size of the pressure shadow is independent of η, but strongly dependent on n. For example, at n=1, pressure shadows are roughly circular in shape, while for n>1, pressure shadows disintegrate into two branches. We also show that pressure may only exceed 100MPa in pressure shadows at resolvable distances from the object if η>4 for strain rates of 10-14s-1 and matrix viscosities around 1022Pas. As these values for strain rate, viscosity and viscosity contrast are geologically reasonable, we emphasise that it is conceivable that geobarometric results obtained from syndeformational mineral parageneses near rigid porphyroblasts may be influenced by non-lithostatic components of pressure.